A Critical Appraisal of Manikya: A Ratna (AYUSHDHARA, 2023)
Rasashastra has used almost all the available metals and minerals in the creation for medicinal purpose. Gems or Ratnas are also one among them. As the priority of Rasashastra was to attain a body (Deha vada), Siddhahcaryas of Rasashastra had used the gems for the purpose of inducing the longevity of life in a human body. Manikya or ruby, the rarest of gemstones and grouped under Ratna Varga. Its use leads to generate the mental and spiritual powers and special divine thoughts rise in mind. Manikya or ruby balances Surya (sun). Surya represents the king of the solar system in Jyotish. It also represents authority, power, self, father, body and health. It is composed of aluminium oxide, chromium and titanium. Manikya is having innovate action on various hormonal, enzymatic, immunological pathways, as it comprises mainstream trace elemental moieties. It is a versatile drug having Medhya, Vrushya property and specially recommended in Dwajabhanga, Kshaya and it has best Rasayana and Vajeekarana property. In the present review an attempt has been made to compile historic review, mythological origin of Manikya, Synonyms according to different Acharyas, Manikya Guna Karma and Dharana punya, types and their Lakshana, Grahyagrahyatva etc. present review expected to furnish the knowledge on Manikya ratna so that it can be widely used in therapeutic practices.